2011
DOI: 10.1111/j.1526-4637.2011.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn from First-Year Medical Students' Perceptions of Pain in the Primary Care Setting?

Abstract: First-year medical students identified pain as a major concern in their early clinical experience. Students' perceptions of pain-related encounters can inform curriculum design and may ultimately benefit both physicians and the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
(20 reference statements)
0
31
0
Order By: Relevance
“…Medical student dissatisfaction with pain education has been reported among students intending to pursue a primary care specialty. 10 The short survey we report in this article shows that this dissatisfaction extends to all University of Washington medical students. There is evidence that increased time educating medical students results in improved knowledge and attitudes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Medical student dissatisfaction with pain education has been reported among students intending to pursue a primary care specialty. 10 The short survey we report in this article shows that this dissatisfaction extends to all University of Washington medical students. There is evidence that increased time educating medical students results in improved knowledge and attitudes.…”
Section: Discussionmentioning
confidence: 82%
“…They concluded, “There are inarguable links between the undertreatment and the maltreatment of pain and the lackluster state of pain education in medicine.” Watt-Watson et al 33 had previously reported the average veterinarian pain curriculum to be 87 hours, prompting Macleans, a leading popular Canadian publication, to satirically announce on its cover, “Your dog can get better health care than you.” 28 The recently published transformational report of the U.S. Institute of Medicine (IOM) about relieving pain in America 23 confirms the self-report of inadequate pain competence of both actively teaching academics and community-practicing physicians, 20,32 as well as the medical students themselves. 4,10,35 The IOM identified the chief problems in medical school education to be “a lack of breadth in the presentation of the topic, a lack of integration of basic science and clinical knowledge, and a lack of clinical role models—especially specialists treating chronic pain—in most academic medical centers.” 23 An urgent training need exists to understand pain as a chronic disease to prevent ever more patients and medical practices from becoming disabled by the challenges of chronic pain.…”
mentioning
confidence: 99%
“…Theme One: Inadequacies of training: Studies have shown that PCPs report a lack of knowledge, education, and training in pain management [16,18,19,24] especially in the area of opioid prescribing. Our study describes similar perceptions.…”
Section: Systems Domainmentioning
confidence: 99%
“…For providers and clinic staff repeatedly encountering PDB, consequences may include inefficiency, stress, and compassion fatigue. 9 Ultimately, the supply of primary care physicians may be adversely affected: negative experiences during medical training with patients exhibiting PDB while receiving chronic opioid therapy may discourage students 10 and residents 9 from a career in primary care. For patients-many of whom may be struggling with an opioid use disorder-continuation of opioid prescriptions may reinforce their maladaptive behaviors.…”
mentioning
confidence: 99%